Load‑bearing behaviors of sandwich plates with non‑uniformly distributed grid cores : Static compression and bending - Hao, Ning; Wang, Youlong; Song, Yiheng; Ruan, Sihan; Quanjin, Ma; Wang, Ziying (Springer, 2023)
Grid-core sandwich plates have wide applications, and non-uniform grid plates (NUGPs) demonstrate greater potential under various loading conditions. In comparison to uniformly distributed grid plates (GPs), we designed a series of NUGPs by varying the lengths of transverse and longitudinal grid walls. We investigated their static compression and three-point bending mechanical properties, deformation modes, and influence mechanisms. The results are as follows: (1) NUGPs exhibit higher compressive strength while majority of them manifest superior energy absorption compared to GPs. A specific category of NUGPs demonstrates superior bending strength and energy absorption performance, indicating its potential in various scenarios. (2) Under compression loading, denser core grids in NUGPs result in more half waves in core deformation. Under bending loading, most NUGPs experience local failure at the loading head, while the specific category surpassing GPs undergoes shear buckling in longer grid walls. (3) Deformation modes of the core layer, mechanical analysis, thin plate buckling theory, and equivalent bending stiffness calculations elucidate the load-bearing mechanisms of NUGPs. These findings enhance topology optimization research for sandwich plates, provide guidance for grid wall arrangements under different loading conditions, and offer insights for designing lightweight sandwich structures.